2015
DOI: 10.1128/cvi.00552-14
|View full text |Cite
|
Sign up to set email alerts
|

Use of IgG in Oral Fluid To Monitor Infants with Suspected Congenital Toxoplasmosis

Abstract: Infants born to mothers who seroconverted for toxoplasmosis during pregnancy are at risk of sequelae. In the case of a negative work-up at birth, congenital infection can be ruled out only by monitoring the disappearance of maternal immunoglobulin G (IgG) transmitted through the placenta, which can be achieved by regular blood sampling during the first year. To alleviate the discomfort of this follow-up, we developed an indirect enzyme-linked immunosorbent assay to detect specific IgG diffusing passively from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 24 publications
1
9
1
Order By: Relevance
“…Previous reports have shown that anti‐ T. gondii IgG, IgM and IgA abs are present in saliva. In some studies, the salivary IgA and IgG levels reflect those in serum, but they show low sensitivity and specificity values, as in the present study . To our knowledge, searches of anti‐ T. gondii IgG subclasses have not been performed in saliva.…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…Previous reports have shown that anti‐ T. gondii IgG, IgM and IgA abs are present in saliva. In some studies, the salivary IgA and IgG levels reflect those in serum, but they show low sensitivity and specificity values, as in the present study . To our knowledge, searches of anti‐ T. gondii IgG subclasses have not been performed in saliva.…”
Section: Discussioncontrasting
confidence: 58%
“…In some studies, the salivary IgA and IgG levels reflect those in serum, but they show low sensitivity and specificity values, as in the present study. [10][11][12][13][14][15][16] To our knowledge, searches of anti-T. gondii IgG subclasses have not been performed in saliva. We hoped they could help diagnose or suggest prognosis, but we found a rather different panorama, as they performed badly, mainly because most positive cases for specific IgG2, IgG3 and IgG4 abs in saliva were negative in serum and did not correlate to IgG abs either; thus, they exhibited very low diagnostic parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interferon gamma released after T-cell stimulation by T. gondii antigens has be proven to be useful for the diagnosis of congenital toxoplasmosis, but it is currently not commercially available ( 27 ). Detection and follow-up of Toxoplasma IgG in oral fluid have also been used to monitor infants with suspected congenital toxoplasmosis, and it is a promising diagnostic tool ( 28 ). In addition, brain imaging studies and retinal exams can also exhibit findings that are highly suggestive of the disease, and in the absence of alternative etiologies and proper clinical context, they can be diagnostic ( Table 1 ).…”
Section: Principles and Methods Available For The Diagnosis Of Congenmentioning
confidence: 99%
“…The use of platforms with multiplex capacities can address cost, with the additional benefit that they may be extended to other infections. In addition, the feasibility of testing for antibodies in body compartments beyond serum, such as whole blood and saliva, can address cost and patient convenience ( 28 ). Lastly, public health authorities and national policies should address the need to fund and protect reference centers of excellence for the diagnosis and management of congenital infections since these infections may not be seen commonly in individual practices or medical centers but are a source of major morbidity and mortality to the fetus and to newborns.…”
Section: Future Directionsmentioning
confidence: 99%